The Effect of Wordwall-Assisted Interactive Learning Media on Students' Learning Interest in Science and Social Studies - Nurlita Aristya Suci; Rizal Rizal; Surahman Wilade; Nashrullah Nashrullah; Putriwanti Putriwanti (Journal of Innovation and Research in Primary Education, 2026)
Learning interest constitutes a critical affective factor influencing students' engagement and academic success in elementary education. However, IPAS (Integrated Science and Social Studies) instruction in many Indonesian elementary schools remains dominated by conventional, teacher-centered approaches that limit student participation and diminish learning interest. This study examined the effect of Wordwall-assisted interactive learning media on Grade III students' learning interest in IPAS at SD Inpres Lolu. Employing a pre-experimental one-group pretest-posttest design, the study involved 23 students selected through saturated sampling. Data were collected using a validated learning interest questionnaire (Cronbach's Alpha > 0.60) administered before and after the two-week Wordwall implementation. Analysis included descriptive statistics and paired-sample t-test following normality verification. Results demonstrated a significant increase in mean learning interest scores from 62.52 (pretest) to 80.04 (posttest), with a moderate N-gain value of 0.46. The paired-sample t-test confirmed statistical significance (p = 0.01 < 0.05), rejecting the null hypothesis. These findings indicate that Wordwall-based interactive media significantly enhance elementary students' learning interest in IPAS by transforming conventional instruction into engaging, game-based experiences. The study contributes empirical evidence supporting game-based learning integration in elementary science education, with implications for instructional practice and professional development. Future research should employ experimental designs with control groups and examine long-term effects on both affective and cognitive outcomes.